Laminin-defined mechanical status modulates retinal pigment epithelium phagocytosis - Kozyrina, Aleksandra N.; Piskova, Teodora; Semeraro, Francesca; Doolaar, Iris C.; Prapty, Taspia; Haraszti, Tamás; Hubert, Maxime; Windoffer, Reinhard; Leube, Rudolf E.; Smith, Ana-Suncana; Di Russo, Jacopo (EMBO Reports, 2025)
Epithelial cells exhibit strong interconnections that are crucial for tissue mechanical properties. In homeostasis, these properties, termed mechanical homeostasis, depend on the balance between intercellular tension and extracellular matrix (ECM) adhesion forces. While age-related ECM remodeling is linked to outer retinal disease, its fundamental role in mechanical homeostasis remains unclear. In our study, we quantified changes in the mechanical state of retinal pigment epithelium (RPE), revealing a correlation with gradients of basement membrane laminins and their integrin receptors, β1 and β4. This relationship is related to regional phagocytic demand for recycling photoreceptor outer segments. Using a reductionist approach, we found that laminin 332 and laminin 511 isoforms differentially influence engagement with β1 and β4 integrins at low densities. Notably, laminin 511 enhances RPE contractility by reducing the β4 to β1 integrin engagement ratio, which subsequently diminishes phagocytic efficiency. Our findings suggest that the ECM-defined mechanical status of RPE serves as a novel parameter for visual function.
CRIS-Team Scopus Importer:2025-05-30
Keywords: ECM; Laminin; Mechanical Homeostasis; RPE